Análise do uso de estímulos auditivos e variações prosódicas no efeito IRAP - Germanna Costa Parreiras Rezende (2024)
The Implicit Relational Assessment Procedure (IRAP) is a procedure that historically has been based solely on visual stimuli to measure verbal relations. In this sense, a modified version of the IRAP software was developed so that the presentation of auditory stimuli was enabled. The present research aims to analyze to what extent auditory-enabled IRAP would impact on the IRAP effect. An experimental study was conducted involving 90 randomly distributed participants among three distinct groups: a group exposed to visual stimuli (control), a group exposed to auditory stimuli with neutral prosody and a group exposed to auditory stimuli with prosodic variations (congruent with the linguistic content). As expected, the IRAP effect could also be observed by analyzing data yielded from auditory-enabled IRAP groups. The results suggest that there was no superiority of the IRAP effect in the group exposed to stimuli with prosodic variation compared to the neutral prosody group, which does not support the study’s original hypothesis. Significant differences were observed between groups for only one trial type and within groups differences in more than one trial type. Such findings may be related to the stimuli that were selected for this study and not to the expected performance for the semantic categories. Alternatively, it could be interpreted that a supposed ease of responding to certain frames in the task outlined in this research. The results also suggest that the use of auditory stimuli appears to maintain the expected effect of the procedure. Findings were further discussed.